2018
DOI: 10.22326/ijiasscience.40
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Development of Explosive Power and Rapidity in Schoolchildren Aged 14-15 Years Old

Abstract: The primary task of physical education is the harmonious development of all anthropological parameters and characteristics of children. Knowing the motor skills of pupils, male and female, is directly related to the effects of physical education classes and the development of individual motor skills. The aim of this research was to determine the differences in the quantitative motor skills between boys and girls. The sample includes a population of 42 primary school students from primary school Serbia in East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In terms of testosterone dynamics, in the tests performed on athlete athletes, we can also mention the authors Joksimovic et al (2018) who demonstrated the same thing.…”
Section: Discussionmentioning
confidence: 68%
“…In terms of testosterone dynamics, in the tests performed on athlete athletes, we can also mention the authors Joksimovic et al (2018) who demonstrated the same thing.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, higher speed and strength is achieved, which helps to improve proprioreceptor (sensation of the relative position of body parts and their movements in a person, that is, the sense of one's body) [7]. Some experimental research with similar objectives for masuring de development of explosive power at children found similar results in long jump test with average length of 168.95 cm in girls [9].…”
Section: Discussionmentioning
confidence: 99%